Hedonic Quality Analysis of Flour-Based Longgi Brownies Cake substituted with Tilapia - Sri Steviana Limbe; Lukman Mile; Nikmawatisusanti Yusuf (Faculty of Fishery and Marine Sciences - Universitas Negeri Gorontalo, 2019)
This study aims to determine the effect of substitution of tilapia (Oreochromis niloticus) flour to the organoleptic characteristics of Longgi (Xanthosoma sagitifolium) flour-based brownies cake. The hedonic quality organoleptic analysis of the data used is the Kruskal-Wallis test parameters, namely the taste, texture, aroma and color. Duncan further test using the test. The results showed that the use of tilapia flour has a real effect on the value of the hedonic quality of taste, texture, aroma and color. Hedonic quality characteristics of the brownies with tilapia flour substitution are of different values range from 5.48 to 8.28 with the criteria for taste “less sweet” to “no sweet taste”; 6.36 to 8.24 with the criteria of texture is less dense to dense; 7.48 to 8.28 with the criteria of color brown to blackish brown and smelling the aroma from 5.36 to 8.04 with the criteria “no scent” to “fragrant aroma”. Keywords: Brownies; longgi; Xanthosoma sagitifolium; tilapia; Oreochromies niloticus; fish flour; quality; substitution; organoleptic.